The influence of environmental cognition on green consumption behavior - Xie, Chi; Wang, Ru; Gong, Xiaoxiao (Frontiers in Psychology, 2022)
With rising consumption and environmental problems, there is an increasing need for green consumption. From a micro perspective, the influence and related mechanisms of environmental cognition on consumers’ green consumption behaviors are examined by multilayer linear analysis and CGSS2010 microdata based on the theoretical model framework of planned behavior. The study shows that (1) environmental cognition positively influences attitudes toward green consumption, green consumption subjective norms, and green consumption perceived behavioral control, which leads to increased intentions to engage in green consumption and actual green consumption behaviors. Environmental cognition can either promote the intention for and lead to green consumption behavior or directly promote green consumption behavior. (2) The more developed a region’s economy is, the stronger people’s attitudes toward green consumption will be, and the greater the perceived external pressure to engage in green consumption becomes, the more likely people will be to develop the intention to engage in green consumption behavior. Regional environmental quality inhibits green consumption intention to a certain extent. (3) The influence of environmental cognition on green consumption shows regional heterogeneity.